2021
DOI: 10.24193/tras.62e.2
|View full text |Cite
|
Sign up to set email alerts
|

The Competency Movement in Public Hospitals: Analysing the Competencies of Hospital Executive Managers

Abstract: "Our primary aim was to provide a quantitative snapshot relying on a self-assessment tool developed for the local healthcare environment and formal tasks for top-level executive hospital managers of public healthcare organizations. We used a cross-sectional and descriptive mixed study design that targeted the nationwide population of 701 top-level managers in public hospitals in 2015 in Turkey. As the first step, position description content analysis was conducted based on document analysis to explore their le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Furthermore, other scholars reported that leadership capabilities are limitedly investigated in most LMICs (14). Moreover, a study by (15) revealed the limited empirical research on leadership competency related issues at the primary healthcare level in developing countries This has resulted to a considerable knowledge gaps on the leadership competency of health managers in the LMICs that substantiate the need to be investigated (14,16). Thus, a reliable information is necessary to unveil the evidence on the leadership competency among primary healthcare facility managers in the LMICs including Tanzania (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other scholars reported that leadership capabilities are limitedly investigated in most LMICs (14). Moreover, a study by (15) revealed the limited empirical research on leadership competency related issues at the primary healthcare level in developing countries This has resulted to a considerable knowledge gaps on the leadership competency of health managers in the LMICs that substantiate the need to be investigated (14,16). Thus, a reliable information is necessary to unveil the evidence on the leadership competency among primary healthcare facility managers in the LMICs including Tanzania (16,17).…”
Section: Introductionmentioning
confidence: 99%